Limits of noise and confusion in the MWA GLEAM year 1 survey - Franzen, T.; Jackson, C.; Callingham, J.; Ekers, R.; Hancock, P.; Hurley-Walker, N.; Morgan, J.; Seymour, N.; Wayth, Randall; White, S.; Bell, M.; Dwarakanath, K.; et al. (SPIE - Internatioal Society for Optocal Engineering, 2015)
The GaLactic and Extragalactic All-sky MWA survey (GLEAM) is a new relatively low resolution, contiguous 72-231 MHz survey of the entire sky south of declination +25. In this paper, we outline one approach to determine the relative contribution of system noise, classical confusion and sidelobe confusion in GLEAM images. An understanding of the noise and confusion properties of GLEAM is essential if we are to fully exploit GLEAM data and improve the design of future low-frequency surveys. Our early results indicate that sidelobe confusion dominates over the entire frequency range, implying that enhancements in data processing have the potential to further reduce the noise.